URBAN CIRCUMSTANCES IN CERNTRAL AND SOUTHERN PARTS OF SERBIA IN THE ERA OF THE KING MILUTIN (Heritage, 2021)
The era of the reign of the King of Milutin represents an important turning point in the history of the medieval Serbia. It cannot be said he was the initiator of either economic or urban development, but it can be noticed in his era there was a considerable step in this direction. The King Milutin himself showed an enviable energy thanks to it he enlarged his state and introduced numerous changes. By annexation of the areas in the south, the part of Serbian state became a territory which inherited the urban culture being inherited from the antique and renewed during the Byzantine rule. By the adoption on Byzantine patterns of behaviour, the urban culture was being adopted as well.  The second important step toward the process of urbanization was the opening of mines and appearance of market places in their vicinity. In the era of the King Milutin in documents for the first time appears seven mining market places: Rudnik, Trepča, Rogozno, Gračanica (Janjevo), Novo Brdo, Lipnik and Trešnjica.Their characteristic was that they represented centres in which in initial period lived Saxons, but by the time local inhabitants will have been moved, which will be dealing with mining industry, craft, commerce and services provision. As the Saxon’s community was restricted and without additional influx, by the time it will have been had assimilated into the Serbian one for those settlements as well. Close to Saxons, at least as per religion, were merchants coming from the Coast, and which were called by domestic population Latins. The King Milutin had issued several charts and letters to citizens of Dubrovnik by which he confirmed privileges and security to them. In that sense, it is important the chart issued in 1302 in Vrhlab. Besides the citizens of Dubrovnik, citizens of other coast towns dwelled in mining market places including some Italian communes due to which they represented multicultural milieu. In the era of the King Milutin these settlements were in their infancy, and the lack of sources did not allow their significant consideration. Nevertheless, those settlements represent a solid fundament and initiator for further urban development which will follow in subsequent decades.
Keywords: The King Milutin, urban development, economy, Serbia, mining market places.